GANTI KERUGIAN DALAM PUTUSAN PRAPERADILAN BAGI TERDUGA TERORIS YANG TERTEMBAK MATI SEBAGAI BENTUK PERLINDUNGAN TERHADAP HAK ASASI MANUSIA - Riyani Kartika Sari, Ni Putu; Suyatna, I Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2013)
Pre-trial shall be defined as preparatory investigation before the court trial held. Pre-trial shall be considered as a means of protection derived from Law towards the defendant or alleged ones or their relatives with the justice-seeking motives when arbitrary measures were committed by the authorized officials. Option to deliver a pre-trial motion shall also be provided towards the relatives or inheritor of alleged terrorist who experienced arbitrary measures during the ambush conducted by the authorized officials. Given the normative legal research to be applied within this writing, it shall also illustrate the pre-trial and certain aspects related alleged terrorist who deceased due to the action constituted by the authorized officials; for instance, the relation between Pre-trial and Human Rights and Compensation derived from the court’s verdict. Compensation within this judgment shall be applied both in material and immaterial means. Such mechanism also promotes the human rights especially towards the offender itself.
Keywords: Pre-trial, Human Rights, Compensation, Terrorism